The potential of phythotherapy in otorhinolaryngology - Domka, Wojciech; Aebisher, David; Bober, Zuzanna; Ożóg, Łukasz; Bartusik-Aebisher, Dorota (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Introduction. The objective of this paper is to review the evidence of the use of herbs in phytotherapy. Aim. To discuss plant properties and applications in otorhinolaryngology. Materials and methods. We analysed literature and collected information of phythotherapy in otorhinolaryngology. Results. The databases were searched using various keywords such as phytotherapy, otorhinolaryngology, and herbs such as: echinacea, eucalyptus, garlic, ginkgo, ginseng, kava, pelargonium sidoides, rosemary, spirulina, St John’s wort, and thyme. Conclusions. Due to the beneficial impact of meicinal plants in medicine there is a growing interest in analytical identification and quantification for clinical medicine and forensic toxicology.
Keywords: phytotherapy; medicinal plants; otorhinolaryngology